Hubungan Antara Kematangan Beragama dan Kesejahteraan Psikologis pada Mahasiswa Semester Akhir - Ahmad Sabilil Alief; Aqeel Putra Hermawan; Muhammad Haikal Hibrizi; Yuminah Yuminah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the relationship between religious maturity and psychological well-being in final year students using a qualitative approach. Final year students are a group that is vulnerable to academic pressure, identity crisis, and anxiety about the future. In this context, religious maturity is believed to play an important role in shaping individuals' perspectives, attitudes, and strategies in facing life's challenges. This study reveals that religious maturity acts as a spiritual foundation that strengthens mental resilience, gives meaning to life experiences, and fosters a sense of optimism. These findings suggest that mature spirituality can be an authentic source of psychological well-being for final year students. This study contributes to a new understanding of the importance of integrating religious aspects in strengthening mental health in higher education environments.